The Price Is Right: Updating Inflation Expectations in a Randomized Price Information Experiment - Armantier, Olivier; Nelson, Scott; Topa, Giorgio; van der Klaauw, Wilbert; Zafar, Basit (The Review of Economics and Statistics, 2016)
Using a unique, randomized information experiment embedded in a survey, this paper investigates how consumers’ inflation expectations respond to new information. We find that respondents, on average, update their expectations in response to (certain types of) information, and do so sensibly, in a manner consistent with Bayesian updating. As a result of information provision, the distribution of inflation expectations converges toward its center and cross-sectional disagreement declines. We document heterogeneous information processing by gender and present suggestive evidence of respondents forecasting under asymmetric loss. Our results provide support for expectation-formation models in which agents form expectations rationally but face information constraints.